Challenges for the Swiss Innovation System - Hans Gersbach; Martin Wörter (ETH Zurich, KOF Swiss Economic Institute, 2024)
The Swiss Innovation System is the most powerful instrument to achieve continuous improvements in material well-being for citizens in Switzerland, and for addressing challenges such as protection against cyberattacks or providing clean energy. Yet, the Swiss Innovation System and its successes are challenged in multiple ways today. The Swiss lead in innovation has declined and the share of firms performing R&D has decreased. Other major countries undertake large-scale industrial subsidies to promote innovation and relocation of economic activities. This raises the question whether the Swiss Innovation System should also be adjusted. The framework of the Swiss economic system-strong focus on basic research, linking public institutions of higher education with industry, and few direct subsidies-is a promising approach for the future. A strong public research sector combined with steady enhancements of the Swiss knowledge and technology transfer capacity, as well as variations of existing instruments at Innosuisse or tax credits at the cantonal level for R&D expenditures could further boost innovation efforts in the private sector. Such measures would also be an appropriate response to international challenges such as the OECD minimum tax. Moreover, the success of the Swiss Innovation System relies crucially on other framework conditions, in particular on the open access to international markets for goods and services and on the ability to attract researchers from around the world as well as on entrepreneurship of residents in Switzerland.
Keywords: 330